Modeling the buffer capacity of ingredients in salad dressing products. Issue 4 (21st March 2020) - Longtin, Madyson; Price, Robert E.; Mishra, Ritu; Breidt, Fred
Abstract : Abstract: The pH of most acid food products depends on undefined and complex buffering of ingredients but is critically important for regulatory purposes and food safety. Our objective was to define the buffer capacity (BC) of ingredients in salad dressing products. Ingredients of salad dressings were titrated individually and in combination using concentrations typical of dressing products. Titration curves from pH 2 to 12 were generated with sodium hydroxide and hydrochloric acid, which were then used to generate BC curves. A matrix of concentration and p K values for a series of monoprotic buffers approximated the pH of each ingredient. Some buffer series required anion or cation corrections for accurate pH prediction, possibly due to the presence of salts of acid or bases. Most buffers had BC values less than 10‐fold the BC of acetic acid (0.25 β ) typically in dressing formulations and had little influence on the final product pH of the dressings tested. Unexpectedly, we found that sugars in dressing formulations, including sucrose or corn syrup, exhibited buffering at pH values greater than 11 (0.035 β and 0.059 β, respectively), which was likely due to weakly acidic hydroxyl groups on the sugar molecules. However, the concentration and p K for buffers above pH 11 or below pH 2 were difficult to quantify due to the BC of water. The BC data may help to quantify the effects of salad dressing ingredients on the final product pH and benefit regulatory agencies and manufacturers in assessing product pH and safety. Practical Application: Buffer capacity data for salad dressing ingredients may help determine the influence ingredient addition will have on the final pH of a salad dressing product. The addition of low acid ingredients with little or no buffering may not significantly alter pH. The modeling method may be useful for regulatory purposes to estimate the effects of low acid ingredients on pH changes for food safety and may also be useful for product development of acid and acidified foods.